PENGARUH PENGGUNAAN MULTIMEDIA INTERAKTIF TERHADAP PEMAHAMAN KONSEP DALAM PEMBELAJARAN MATEMATIKA DI MTs DARUL ULUM MUHAMMADIYAH GALUR - Ika Septi Hidayati; Toto Hermawan; Erna Setyawati (Intersections, 2020)
At the time of the Covid-19 pandemic, all learning was carried out online or online learning, while schools and students had to follow the existing curriculum in their schools, which of course not all of their lessons were happy. Mathematics is one of the subjects that is always a scourge for students, regardless of those who enjoy mathematics. The reasons vary, some say the lessons are difficult to understand, students are not interested in learning mathematics, the teachers are boring, and so on. So that many parents of students who provide additional tutoring for their children by hiring math teachers, in the hope that their children are mathematically intelligent. This study aims to examine the effect of using animated interactive multimedia on students' understanding of the concept of understanding mathematical concepts. The population of this study were students of class VII MTs Darul Ulum Muhammadiyah Galur even semester of the 2019/2020 school year. Of the five existing classes, two classes were taken randomly as samples with one class as the experimental class and one class as the control class. This study used the randomized pretest-posttest control group design. The research data were obtained through a test in the form of a description of the rectangular and square material. The results showed that there was a difference in the understanding of mathematical concepts in students who used animated interactive multimedia higher than the understanding of mathematical concepts of students who took conventional learning, and there was a positive and significant effect of the use of animated interactive media on the Mathematical Concept Understanding of Class VII MTs Darul Ulum Muhammadiyah Galur Tahun Students 2019/2020 Teaching